(untitled) (Research, Society and Development, 2023)
Dental enamel is a mineralized tissue formed by ameloblasts and when there is a failure at some stage of its formation, it is called amelogenesis imperfecta (AI). Therefore, this study aims to review the literature on dental formation, classifications, characteristics and treatment of UA. This is a qualitative descriptive study carried out through a bibliographic survey of scientific articles published in recent years relevant to the subject. Variations in AI treatment vary by socioeconomic status, age, subtype, and severity. Its implications can cause aesthetic problems, tooth sensitivity, loss of vertical dimension, association with tooth impaction, gingival inflammation, prevalence of caries, delayed eruption and anterior open bite are also reported. With minimally invasive adhesive rehabilitative techniques, damage is minimized, especially in younger patients, so that dental development and aesthetics are not impaired. With advancing age, treatment is complex and integrated. Therefore, restorative treatment must restore health, function and aesthetics with a focus on the patient’s quality of life, who must remain in periodic follow-up.